1976
DOI: 10.1055/s-0028-1097649
|View full text |Cite
|
Sign up to set email alerts
|

TRITERPENOIDS OFADENANTHERA PAVONINABARK

Abstract: A. pa v o n i n a bark yielded saponin having glucose as the sugar moiety and oleanolic a n d echinocystic acids as sapopenins. These acids were also isolated in free state, besides stigmnsterol glucoside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The leaves possess octacosanol, dulcitol, glucosides of β-sitosterol and stigmasterol. The bark furnishes stigmasterol glucoside, and pods contain glycosides, saponins and steroids [9][10][11] . A new five-membered lactone ring with an exo-cyclic double bonded compound, pavonin was isolated from the its methanol soluble part 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The leaves possess octacosanol, dulcitol, glucosides of β-sitosterol and stigmasterol. The bark furnishes stigmasterol glucoside, and pods contain glycosides, saponins and steroids [9][10][11] . A new five-membered lactone ring with an exo-cyclic double bonded compound, pavonin was isolated from the its methanol soluble part 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the ground seed is widely used for the treatment of various human ailments such as treatment of boils, inflammation, blood disorders, arthritis, rheumatism, cholera, paralysis, epilepsy, convulsion, spasm and indigestion (Burkill 1966 ; Balogun and Fetuga 2004 ). Phytochemically, the seed and pod contain glycosides, saponins and steroids (Howes 1974 ; Yadav et al 1976 ). A new five-membered lactone ring compound, pavonin was isolated from the methanol soluble part of A. pavonina (S.A.Muhammad et al 2005 ), oil extracted from the seed has been reported to have membrane-stabilizing activity by reducing lytic effect on erythrocytes, exhibited by many intravenous drugs (Anna et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the ground seed is widely used for the treatment of various human ailments such as treatment of boils, inflammation, blood disorders, arthritis, rheumatism, cholera, paralysis, epilepsy, convulsion, spasm and indigestion (Burkill, 1966;Balogun & Fetuga, 2004). Phytochemically, the seed and its pod contain glycosides, saponins and steroids (Howes, 1974;Yadav et al, 1976). A new five-membered lactone ring compound, parvonin was isolated from the methanol soluble part of A. pavonina oil extracted from the seed has been reported to have membrane-stabilizing activity by reducing lytic effect on erythrocytes, exhibited by many intravenous drugs (Muhammad et al, 2005;Anna et al, 2006).…”
Section: Introductionmentioning
confidence: 99%